2019
DOI: 10.1039/c9ra07255a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic growth of rhombic dodecahedral Cu2O crystals controlled by reaction temperature and their size-dependent photocatalytic performance

Abstract: Compared with low-index {100} or {111} planes of Cu2O crystals, rhombic dodecahedra (RD) Cu2O crystals exposing 12 {110} facets exhibit the most superior photodegradation of organic pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Furthermore, as given in Table S1, the bandgap ( E g ) of composites calculated with the Kubelka–Munk equation suggested that the E g of CuCN- T s was reduced with loading Cu NPs, resulting in the boosting number of photoexcited charges . After carefully comparing the calculated E g , we also found that the E g slightly decreased with the increase of solvothermal temperature; in other words, it decreased with the increase of Cu NP size, confirming that the size effect of Cu NPs influence E g to a certain extent. , A similar phenomenon was also reported in previous works, which may be attributed to the high conduction band and the depressed valence band. , Nevertheless, it should be noted that the introduction of Cu particles does not display a significant impact on E g , which may be ascribed to the too-low loading of Cu (1–2%). This suggests that all of the photogenerated electrons produced by materials with smaller Cu NPs have higher energy, which provides a stronger thermodynamic driving force for reducing carbon dioxide to methanol.…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, as given in Table S1, the bandgap ( E g ) of composites calculated with the Kubelka–Munk equation suggested that the E g of CuCN- T s was reduced with loading Cu NPs, resulting in the boosting number of photoexcited charges . After carefully comparing the calculated E g , we also found that the E g slightly decreased with the increase of solvothermal temperature; in other words, it decreased with the increase of Cu NP size, confirming that the size effect of Cu NPs influence E g to a certain extent. , A similar phenomenon was also reported in previous works, which may be attributed to the high conduction band and the depressed valence band. , Nevertheless, it should be noted that the introduction of Cu particles does not display a significant impact on E g , which may be ascribed to the too-low loading of Cu (1–2%). This suggests that all of the photogenerated electrons produced by materials with smaller Cu NPs have higher energy, which provides a stronger thermodynamic driving force for reducing carbon dioxide to methanol.…”
Section: Resultssupporting
confidence: 66%
“… 43 Specially, the ratio of the peak intensity of (220) peak to that of the (200) facet significantly differ between the various particles, suggesting the growing fractions of {110} facets. 15 …”
Section: Resultsmentioning
confidence: 99%
“…43 Specially, the ratio of the peak intensity of (220) peak to that of the (200) facet signicantly differ between the various particles, suggesting the growing fractions of {110} facets. 15 The average crystal size of the resulting microcrystals are calculated, as shown in Table S2, † which are according to the Debye-Scherer formula (D ¼ 0.89l/b cos q, where l is the X-ray wavelength (1.5418 Å), q is the Bragg diffraction angle of the peak, and b is the peak width at half maximum). 44 To determine the chemical compositions of the obtained Cu 2 O crystals and to identify the chemical state of Cu in the samples, wide-range and high-resolution XPS spectra were obtained, and only Cu and O were observed in the spectra (Fig.…”
Section: Morphology Analysis Of Cu 2 O Crystals Via Tuning the Amounts Of Oh à Ionsmentioning
confidence: 99%
See 2 more Smart Citations